Recipes for Change validation report: Lamb tagine with Moroccan Truffles - Norman, James (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The main climate risks to truffle availability in the highlands of eastern Morocco are: (i) increased prevalence of drought due to decreased levels of rainfall and increased rainfall variability and (ii) increased average and extreme temperatures. It is also noted that the combined effect of these two main climate impacts could further accelerate the desertification process already observed in the region. The particular response of pastoral systems to these climatic stresses is uncertain, yet it appears unlikely that current pressures of overgrazing in the region would be lessened. The key adaptation measure for managing the foreseen impacts of climate change within the region relates to improved livestock management practices. In addition to this, regardless of possible future changes in climate stressors, the inherent vulnerability of pastoral livelihoods in the region indicates that adaptation measures which incorporate income generation and diversification are of key importance. In light of the literature review conducted, CCAFS validates the climate threats and solutions highlighted in the IFAD statements below: IFAD-identified climate threats to terfass:  Desertification & drought  Prolonged hot and cold weather  Overgrazing ASAP solutions:  Diversification of crops & income generation  Livestock management for soil regeneration  Promotion of water-efficient horticulture systems